NILAI-NILAI KREATIVITAS SISWA DALAM PEMBELAJARAN SENI RUPA MATERI DAUR ULANG MENGGUNAKAN MODEL PJBL SD 6 JEKULO - Nailul Khoiris Sobah; Nur Fajrie; Ika Ari Pratiwi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
It is very important for teachers to provide learning while simultaneously honing students' creativity. As in SD 6 Jekulo in the fine arts subject of recycling material. The class teacher encountered a problem that the majority of fourth-grade students were not optimal and had difficulty expressing their creativity. Due to this, the fourth-grade teacher provided learning with the Project Based Learning model to hone students' creativity. The purpose of this study was to analyze the creativity values of fourth-grade students in fine arts learning using the Project Based Learning learning model at SD 6 Jekulo. The research method was narrative qualitative. Data collection was in the form of observation, interviews, and documentation. The research subjects were fourth-grade students at SD 6 Jekulo. The research data collection techniques were data collection, data reduction, data presentation, and conclusions. The results showed that learning using the Problem Based Learning learning model made it easier for teachers to hone students' creativity. The values of student creativity that were seen based on student behavior when creating works were the values of student independence, student curiosity, and student imagination. These creative values encouraged students to express their imagination. The conclusion of the study with the Project Based Learning learning model used by teachers to teach made it easier for students to hone their creativity in creating works.